Research Trends On Character Education Based On Scopus Database From 2018 To 2023: A Bibliometric Analysis - Sumiharsono, Rudy; Nasaruddin, Nasaruddin; Safrudin, Moh; Ramadhan, Syahrul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This article presents a bibliometric analysis of research trends in "Character Education" based on the Scopus database from 2018 to 2023. Data collection involved 569 metadata of relevant articles in the field of character education from reputable sources. The study aims to provide a comprehensive insight into the scientific development in the field of character education and identify key topics and contributors in academic studies during this period. The bibliometric analysis method was used to examine research trends, topic classifications, and author and institutional collaborations. The research results indicate that character education has become a significant issue in the realm of education during this timeframe, with a noteworthy growth in research attention. Top contributing authors and university affiliations were also identified, highlighting inter-institutional collaborations and continuity in building knowledge in the field of character education. The findings from this bibliometric analysis can provide direction and guidance for academics, researchers, and practitioners in developing more effective character education strategies that positively impact moral and ethical development among students and individuals in society. This article has the potential to make a significant contribution to understanding trends and future directions in "Character Education" research and enhancing comprehension of the challenges and opportunities in this field.